KEDUDUKAN POLITIK PEREMPUAN DALAM METAFORA MASYARAKAT MINANGKABAU - Idris, Nurwani (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2010)
This study examines the meaning of metaphors of women in Minangkabau community, which are expressed in the form of praise to the wise and high position of women. The praise for women in the methaporic discourse does not mean the same thing in its reality. Politically, such praise for women can be a trap for women’s position and freedom. Politics is closely related to the power of words, and many politicians often manipulated the words through metaphors to create political realities that are many times untrue. It is also used to change the impossibilities to be posible to attract followers. The manipulation of the metaphors are used to marginalize women in public sphere, as well.